Blakea viridis (Melastomataceae, Pyxidantheae), a new species from southern Peru - Riva-Regalado, Sebastián G.; Michelangeli, Fabián A. (Phytotaxa, 2025)
Blakea viridis (Melastomataceae: Pyxidantheae), a new species from southern Peru is described. Blakea viridis is characterized by having floral pedicels 5.7–6 cm long, greenish petals 10 mm long, and greenish bracts, which provided the reason for the epithet. This new species is known from only three collections from within the Cusco region of Peru.